1999
DOI: 10.1016/s0039-6028(99)00215-0
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and disproportionation reaction of OH on Ag surfaces: dipped adcluster model study

Abstract: The adsorption and surface disproportionation reactions of OH on various silver surfaces were studied by the dipped adcluster model (DAM ) combined with ab initio HF and MP2 methods. Our studies show that OH binds strongly to Ag surfaces; the adsorption energies were calculated to be 118.3 kcal mol−1 at the short bridge site on Ag(110), 108.6 kcal mol−1 at the fourfold hollow site on Ag(100), and 97.3 kcal mol−1 at the threefold hollow site on Ag(111). The H-O axis is preferentially perpendicular to the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 50 publications
(76 reference statements)
3
15
0
Order By: Relevance
“…However, the specific adsorption of anions would be expected to depend on the concentration even when not discharged 11c. Retention of the negative charge by OH - is in agreement with density functional theory (DFT) calculations, Hartree−Fock calculations, , and dipped adatom cluster calculations . It is also consistent with the suggestion of Guidelli et al that charge transfer does not occur for halides at coverages less than ∼0.25 ML. 3g,7b …”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…However, the specific adsorption of anions would be expected to depend on the concentration even when not discharged 11c. Retention of the negative charge by OH - is in agreement with density functional theory (DFT) calculations, Hartree−Fock calculations, , and dipped adatom cluster calculations . It is also consistent with the suggestion of Guidelli et al that charge transfer does not occur for halides at coverages less than ∼0.25 ML. 3g,7b …”
Section: Resultssupporting
confidence: 87%
“…The latter revealed also that surface oxide formation on Ag(111) proceeds by a 2D nucleation and growth mechanism. Hu and Nakatsuji, using the dipped adcluster model, simulated the interaction of two OH species adsorbed at neighboring sites of Ag(100) surfaces and showed that their disproportionation to form adsorbed oxygen and water is favorable for particular adsorbate bondings . Disproportionation of two OH to form surface oxide would also be expected from the inorganic chemistry of silver: it is well-known that Ag(I) forms stable oxide but not hydroxide.…”
Section: Resultsmentioning
confidence: 99%
“…7 Indeed, this configu-ration turned out to be slightly more stable than adsorption at threefold hollows according to dipped adcluster model calculations. 9 We present here a low temperature STM study of the H 2 O interaction with O / Ag͑110͒ at a crystal temperature T = 250 K. In accord with previous literature, 5,6 we observe that exposure to water causes the complete removal of the O-Ag chains and that the OH groups generated in the reaction form a superstructure consisting of OH rows aligned in the ͗110͘ direction. We find hydroxyls to sit in the valleys between the Ag rows, slightly displaced towards the threefold hollows.…”
Section: Introductionsupporting
confidence: 82%
“…Density functional theory calculations indicate indeed the highly coordinated fourfold and threefold hollow sites as the most stable for OH adsorption at Ag͑100͒ and Ag͑111͒, respectively. 9,14,15 For Ag͑110͒ the assignment is more debated since both adsorption at the short-bridge site in a con-figuration with the OH axis strongly tilted 7,9 and adsorption at threefold hollows 5 have been proposed. Our observation that OH sits in the channels of Ag͑110͒ strongly supports adsorption at threefold hollows.…”
Section: Resultsmentioning
confidence: 99%
“…Previous study has displayed that MP2 misestimated the relative energy of the C 2v isomer of CO 3 to its D 3h analogue and the adsorption energy of CO 3 on Ag(100) could then be largely overestimated by MP2. Similarly, MP2 overestimated the adsorption energy of OH on Ag(100) by 30 kcal mol −1 [36,37]. In addition, another tri-coordinated (tri-coord) near-parallel structure is found, which is 2.1 kcal mol −1 higher in energy than the bi-coordinated perpendicular structure.…”
Section: Adsorption Of Co 3 On Ag(100)mentioning
confidence: 89%